1985
DOI: 10.1159/000176987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thiamin Status on the Metabolism of Linamarin in Rats

Abstract: The effect of graded levels of thiamin on the metabolism of linamarin was investigated in rats. It was observed that on a diet deficient in thiamin, a large amount of linamarin was recovered unchanged in the urine, together with significantly more thiocyanate (SCN) relative to the control. The least amount of thiocyanate (p < 0.05 relative to control) was found in animals receiving the highest amount (twice daily requirement) of thiamin in the diet; but the amount of unmetabolized linamarin was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…Chronic cyanide exposure associated with the consumption of cassava has been associated with a number of cyanide induced disorders including: goiter, dwarfism, and tropical ataxic neuropathy. This is particularly a problem in regions of the world where cassava is the major source of calories (2,22,26,28).Our interest has been to develop strategies for the effective detoxification of cassava food products which would be compatible with the beneficial aspects of cyanogenesis, i.e. protection of the plant against herbivory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic cyanide exposure associated with the consumption of cassava has been associated with a number of cyanide induced disorders including: goiter, dwarfism, and tropical ataxic neuropathy. This is particularly a problem in regions of the world where cassava is the major source of calories (2,22,26,28).Our interest has been to develop strategies for the effective detoxification of cassava food products which would be compatible with the beneficial aspects of cyanogenesis, i.e. protection of the plant against herbivory.…”
mentioning
confidence: 99%
“…hydrolyzed in the body releasing cyanide (2,26,28). Chronic cyanide exposure associated with the consumption of cassava has been associated with a number of cyanide induced disorders including: goiter, dwarfism, and tropical ataxic neuropathy.…”
mentioning
confidence: 99%
“…This qualitative difference may be support of the difference in aromatic typical of these foods (Umoh et al, 1985;Onyango et al, 2004;Lasekan and Abbas, 2010).…”
Section: Resultsmentioning
confidence: 71%
“…Thiamine deficiency has also been implicated in the aetiology of TAN. The experimental study of Umoh et al (1985) on the effect of thiamine status on the metabolism of linamarin in rats has also complemented this 34 D.C. MATttANGI AND A. NAMASIVAYAM hypothesis. As we have not included a group with B12 deficiency in this study we are unable to confirm these findings.…”
Section: Role Of Vitamin B12mentioning
confidence: 88%
“…The experimental study of Umoh et al (1985) on the effect of thiamine status on the metabolism of linamarin in rats has shown that thiamine deficiency causes accumulation of unmetabolized linamarin and free cyanide. The studies of Kamalu (1991) on dogs have also shown some changes in the cassava fed animals which did not match the cyanide fed dogs, hence concluded that some factor in cassava other than cyanide, probably intact linamarin, could have caused the observed pathological changes.…”
Section: Role Of Linamarinmentioning
confidence: 99%